Seroprevalence of anti-Leptospira IgG and IgM among the urban poor communities in Wilayah Persekutuan, Kuala Lumpur - Mohd Zain, S.N.; Mohd Hanapi, I.R.; Nai Chuan, S.; Sahimin, N. (2018)
Malaysia has undergone cumulative growth of urbanization from 43.2% (1989) to 71% (2010) resulting in and urban population boom from 27% (1970) to 71% (2010) 18 and a downward trend in the incidence of urban poverty over the past three decades from 16.5% in 1970 to 3.8% in 2009. However, urban poor communities till exist in pockets of the cities. Leptospirosis is a zoonotic disease caused by pathogenic bacteria from the genus Leptospira. Human infection is known to be associated with poor waste management, in additional to recreational, occupational, or domestic activities. Infection is primarily acquired through contact with soilor water contaminated with the urine of carrier animals primarily rodents.